Difficulties in the Management of Placenta Accreta Spectrum in Hospitals with Limited Resources - Aguilera, Lorgio Rudy; Mojica-Palacios, Luz Mariana; Urquizu, Federico; Gorena, Mirko; Tinajeros Guzmán, Freddy; Vergara Galliadi, Lina María; Hidalgo, Alejandra; Nieto-Calvache, Albaro José (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2022)
Objective Placenta accreta spectrum (PAS) is a serious diseases, and the recommendation is that the treatment is conducted in centers of excellence. Such hospitals are not easy to find in low- and middle-income countries. We seek to describe the process of prenatal diagnosis, surgical management, and postnatal histological analysis in a low-income country referral hospital with limited resources.Methods A descriptive, retrospective study was carried out including patients with a pre- or intraoperative diagnosis of PAS. The clinical results of the patients were studied as well as the results of the prenatal ultrasound and the correlation with the postnatal pathological diagnosis.Results In total, 129 patients were included. Forty-eight of them had a prenatal PAS ultrasound diagnosis (37.2%). In the remaining 81 (62.8%), the diagnosis was intraoperative.Although hysterectomy was performed in all cases, one-third of the patients (31%) did not have a histological study of the uterus. In 40% of the patients who had a histological study, PAS was not reported by the pathologist.Conclusion The frequency of prenatal diagnosis and the availability of postnatal histological studies were very low in the studied population. Surgical skill, favored by a high flow of patients, is an important factor to avoid complications in settings with limited resources.
Keywords: placenta accreta; developing countries; Latin America